Age and the relative importance of liver‐related deaths in nonalcoholic fatty liver disease. Issue 2 (15th February 2023) - Lin, Huapeng; Yip, Terry Cheuk‐Fung; Zhang, Xinrong; Li, Guanlin; Tse, Yee‐Kit; Hui, Vicki Wing‐Ki; Liang, Lilian Yan; Lai, Jimmy Che‐To; Chan, Stephen Lam; Chan, Henry Lik‐Yuen; Wong, Grace Lai‐Hung; Wong, Vincent Wai‐Sun
Abstract : Background and Aims: It is unclear if the leading causes of death in patients with NAFLD differ by age. We aimed to investigate if the relative importance of liver‐related deaths is lower and overshadowed by cardiovascular and cancer‐related deaths in the elderly population. Approach and Results: We conducted a territory‐wide retrospective cohort study of adult patients with NAFLD between 2000 and 2021 in Hong Kong. The outcomes of interest were all‐cause and cause‐specific mortality. Age groups at death were studied at 10‐year intervals. During 662, 471 person‐years of follow‐up of 30, 943 patients with NAFLD, there were 2097 deaths. The top three causes of death were pneumonia, extrahepatic cancer, and cardiovascular diseases. Liver disease was the sixth leading cause of death in patients aged 70–79 and 80–89 years, accounting for 5.1% and 5.9% of deaths, respectively, but only accounted for 3% or fewer of the deaths in the other age groups. Nonetheless, liver disease was the leading cause of death in patients with NAFLD‐related cirrhosis, accounting for 36.8% of all deaths. The incidence of liver‐related death was higher in men younger than age 70 but higher in women afterwards. The incidence of liver‐related death in women increased from 0.62 to 7.14 per 10, 000 person‐years from age 60–69 to 70–79 years. Conclusion: The relative importance of liver‐related death increases with age in patients with NAFLD, especially among women. In patients with cirrhosis, liver disease is the leading cause of death. Abstract :